(3Rjf GdCdMGf aj Yde GdJCdja hGdChRGfs - (3YeQ (B((3Ch (B: (3Wg(B) (3Hf eMeO Hf aJhM GdHjbhfj,J (B1080 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HJCdja GdfZeGJ GdTgjI ai CHYGO WHbGJ GdSehGJ GdYdjg s
(3BNQgG (B:s
(3dCf GdZGjI ef GdHMKjf ai gPG Gdaf, hgh MUhd eYQaI cjajI JCdja GddMf JMUd HOhfg CjVkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B44s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B61 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI eUhQI ef fSNI fhQ YKeGfjI (B((3afhf LejdI (B350) s
Keywords: (3GdehSjbi hGdZfGAs